The Role of Students’ Motivation and Self-Concept as Predictors of Mathematics Performance in Secondary Schools - Abiodun, T.O.; Chinaka, T. W.; Asanre, A. A. (Universitas Pendidikan Indonesia (UPI), 2025)
Student performance in mathematics remains a significant concern in secondary education, particularly because many learners struggle due to low motivation and poor self-concept. This study aimed to investigate how students’ motivation and self-concept predict their performance in senior secondary school mathematics in Ogun State, Nigeria. A descriptive survey research design was employed, involving 306 Senior Secondary School Two (SSS2) students selected through simple random sampling. Data were collected using a Mathematics Performance Test, Mathematics Self-concept Scale, and Mathematics Motivation Questionnaire. The findings revealed that both students’ motivation and self-concept showed a significant and positive relationship with mathematics performance because students who believed in their abilities and were motivated performed better. Together, these factors explained the variance in mathematics achievement. This study underscores the importance of enhancing motivation and self-concept to improve mathematics performance, offering valuable insights for educators and policymakers to strengthen mathematics education outcomes.